EVALUASI FORMULASI KEBIJAKAN SMART VILLAGE PROVINSI LAMPUNG - Mira Fitriana; Dedy Hermawan; Susana Indriyati Caturiani (Wacana Publik, 2021)
This study aims to evaluate the formulation of policies regarding implementing regulations and determining the locus of the Smart Village program in Lampung Province through issues of process, content and policy form. The type of research used is descriptive with a qualitative approach. The data is generated from interviews with sources, observations and documentation. The results of the study found that the program policy formulation process used an institutional approach, namely the Lampung Province Community Empowerment, Village and Transmigration Service as a policy formulator in coordination with the Lampung Province Regional Development Planning Agency and harmonization of regulations with the Lampung Province Regional Secretariat Legal Bureau. The content of the program policy is in accordance with the problems in the village and the strategic issues of the village in Lampung Province as well as the objectives to be achieved in the smart village concept. The form of program policies is in accordance with macro, micro and word for word forms in accordance with the guidelines for the preparation of regional legal products as stipulated in the Minister of Home Affairs Regulation Number 80 of 2015 concerning the Formation of Regional Legal Products. In the future, it is hoped that the Lampung Province smart village policy formulation will also prioritize a bottom-up approach. In order to strengthen implementation, it is imperative that a master plan and other technical policies be established immediately. In the context of monitoring and evaluation so that it is not only carried out by the Lampung Provincial Government, but also from the village government and village communities as program recipients so that it becomes an improvement in the process of formulation and implementation of the next Lampung Province smart village policy.